Anodization Of Zirconium For The Formation Of High-K Dielectric Zirconia (Zro2) Thin Film - Abidin, Noor Rehan Zainal (2011)
Zirconia (ZrO2) is a promising material for future high-k gate dielectric applications. With the decreasing of the get dielectric thickness (<1.4nm), silicon dioxide (SiO2) layer suffered from basic problem of high tunneling leakage current due to its low dielectric constant (k=3.9). ZrO2 has a potential to overcome the tunneling leakage current problem since it has a high dielectric current (k=25) and good thermal stability on silicon (Si) substrate. The main objective of this work is to produce ZrO2 thin film with good properties and suitable for get dielectric application. ZrO2 thin film has been produced by anodizing zirconium (Zr) thin film sputtered on n-type Si substrate.